Palmitic Acid Downregulates Thyroglobulin (Tg), Sodium Iodide Symporter (NIS), and Thyroperoxidase (TPO) in Human Primary Thyrocytes: A Potential Mechanism by Which Lipotoxicity Affects Thyroid? - Meng Zhao; Xiaohan Zhang; Ling Gao; Yongfeng Song; Chao Xu; Chunxiao Yu; Shanshan Shao; Jiajun Zhao (International Journal of Endocrinology)
Our previous studies suggested that the thyroid might be a target organ affected by lipotoxicity, which might be partially related to the increasing prevalence of subclinical hypothyroidism. However, the underlying molecular mechanism is not yet clearly established. This study aimed to assess the effect of palmitic acid stimulation on thyrocyte function. Upon palmitic acid stimulation, intracellular contents of lipids, as well as the expression and activity of three key molecules in thyroid hormone synthesis (i.e., thyroglobulin, sodium iodide symporter, and thyroperoxidase), were determined in human primary thyrocytes. The contents of BODIPY® FL C16 (the fluorescently labeled palmitic acid analogue) entering into the thyrocytes were gradually increased with time extending. Accordingly, the intracellular accumulation of both triglyceride and free fatty acids increased in dose- and time-dependent manners. The effect of palmitic acid stimulation on thyroid hormone synthesis was then determined. Both the mRNA and protein levels of thyroglobulin, sodium iodide symporter, and thyroperoxidase were decreased following palmitic acid stimulation. Consistently, upon palmitic acid stimulation, the secreted thyroglobulin levels in supernatants, 131I uptake, and extracellular thyroperoxidase activity were all decreased in a dose-dependent manner. Our results demonstrated that upon palmitic acid stimulation, the expressions of the key molecules (thyroglobulin, sodium iodide symporter, and thyroperoxidase) were reduced and their activities were suppressed, which might lead to impaired thyroid hormone synthesis.